Evening early childhood education and care: Reformulating the institutional culture. (December 2020) - Salonen, Eija; Sevón, Eija; Laakso, Marja-Leena
The article investigates the ongoing reformulation of the institutional culture of early childhood education and care (ECEC) in Finnish evening ECEC. Educators' practices in implementing evening ECEC were explored and viewed through the lens of young children's belonging. Data were collected by observing the evenings of eight children aged 20–36 months in two Finnish centers offering flexibly scheduled ECEC and analyzed using qualitative thematic analysis. Three main themes of educators' practices were identified: (1) managing a unique and changing social group, (2) fostering homeliness, and (3) maintaining routines and institutional order. While these practices mostly contributed to child-responsive interactions supportive of young children's belonging, in some of them individual children's initiatives were not responded to, thereby challenging their belonging. Overall, educators' practices in implementing evening ECEC manifested the orientation of the institutional culture of ECEC toward the present ideals regarding young children's belonging.